2021
DOI: 10.21037/qims-20-1151
|View full text |Cite
|
Sign up to set email alerts
|

What is new in computer vision and artificial intelligence in medical image analysis applications

Abstract: Computer vision and artificial intelligence applications in medicine are becoming increasingly important day by day, especially in the field of image technology. In this paper we cover different artificial intelligence advances that tackle some of the most important worldwide medical problems such as cardiology, cancer, dermatology, neurodegenerative disorders, respiratory problems, and gastroenterology. We show how both areas have resulted in a large variety of methods that range from enhancement, detection, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 81 publications
0
18
0
Order By: Relevance
“…The overall accuracy of these scores has been found to be modest. Artificial intelligence (AI) is currently being integrated with conventional diagnostic methods in the hopes of performance improvement [14]. In a recent metaanalysis of 13 studies, it was shown that AI significantly improves the diagnosis of NAFLD, NASH, and liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…The overall accuracy of these scores has been found to be modest. Artificial intelligence (AI) is currently being integrated with conventional diagnostic methods in the hopes of performance improvement [14]. In a recent metaanalysis of 13 studies, it was shown that AI significantly improves the diagnosis of NAFLD, NASH, and liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Automatic CAC quantification on non-gated chest CT is particularly cumbersome because of high noise, low resolution, and motion artifacts (13,28). The solutions to tackle this challenging task should be focused on the following: (I) accuracy, i.e., maintaining good consistency with the gold standard; (II) reliability, i.e., maintaining good consistency with manual results on chest CT; (III) easy interpretation, i.e., pixels that contribute to the calcium score are well classified in a single forward pass.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, considering that the spatial attention module only focuses on the target region and the channel attention mechanism only focuses on the local information of each channel, researchers have proposed a mechanism based on the mixed domain, such as convolutional block attention module (CBAM) (14) and residual attention learning (15). However, although CNN-based deep learning methods have made significant progress in the field of medical image segmentation (16,17), a bottleneck remains.…”
Section: Introductionmentioning
confidence: 99%
“…However, most transformer-based methods require pretraining on large datasets to achieve satisfactory performance, yet large datasets and labels with high quality images are very expensive to obtain in the field of medical image segmentation. Some researchers have made related attempts to improve the adaptability of transformer-based methods to small datasets (16,18,27). The most typical work is medical transformer (MT) which was proposed by Valanarasu et al (18).…”
Section: Introductionmentioning
confidence: 99%